Peningkatan Hasil Belajar IPA pada Pembelajaran Tema 9 Melalui Model Discovery Learning Berbantuan Media Powerpoint bagi Siswa Kelas V SDN 2 Tanggung - Mila Deviana; Ervina Eka Subekti; Kuswandari Kuswandari (Jurnal Paedagogy, 2021)
This study aims to improve the learning outcomes of fifth graders at SDN 2 Responsibilities in science subjects with the discovery learning model assisted by power point media. This research method used classroom action research with 3 cycles. The subjects of this study were the fifth grade students at SDN 2 Responsibility with a total of 26 people. Data collection techniques are carried out through interviews, observation, documentation. The data analysis technique used descriptive analysis. The results of this study are that there is an increase in the percentage of students' science mastery learning outcomes, from the first cycle to the third cycle there is an increase in the percentage of science learning mastery outcomes by 73%. So the conclusion obtained from the results of this study is that the discovery learning model assisted by power point media can improve the learning outcomes of fifth grade students of SDN 2 Responsibility in science subjects.